'Prized assets of a ghost economy': Some notes on The Unreturning. Issue 1 (1st December 2016) - Malone, Martin
This article explores aspects of the creative strand of the author's research into Great War poetry and twenty-first-century legacies of the war itself. Whilst one of the two accompanying poetry collections retains a more discernible resemblance to the prevailing mode of lyric elegy, his prose poem sequence, The Unreturning, consciously seeks to disrupt this tradition by adopting the less common neo-modernist poetics of writers such as Geoffrey Hill. What follows is a brief discussion of work-in-progress towards the creation of more resonant and meaningful contexts for our remembrance of a century-old conflict that continues to enjoy extraordinary levels of cultural and political privilege in the United Kingdom.